An evaluation of the FRIENDS for Life intervention with an autistic spectrum population: evaluating the impact on children's anxiety - Slack, Gemma (2013)
This study presents an evaluation of the FRIENDS for Life program (Barrett, 2010) with an autism spectrum (AS) population. FRIENDS for Life is an intervention program underpinned by the principles of cognitive behavioural therapy (CBT) with a primary aim of reducing participant anxiety levels (Barrett, 2010). Existing research suggests it is an effective intervention in reducing participant anxiety levels (Briesch, Hagermoser Sanetti and Briesch, 2010) and it has been recognised by the World Health Organisation (2004) as the only evidence based program effective in reducing anxiety as a universal and targeted intervention. In recent years an evidence base for the application of CBT with children with AS has emerged, though primarily this research has been conducted in a clinical setting. Therefore this study aims to contribute to both evidence bases through implementing the FRIENDS for Life program within a new population as well as contributing to the broader evidence base evaluating the effectiveness of CBT with children with AS.